DAMPAK PEMBELAJARAN MULTIKULTURAL DALAM PELAJARAN AGAMA KATOLIK KELAS XII BAGI PENGEMBANGAN MULTIKULTURALISME - Antonius Virdei Eresto Gaudiawan; Albert I Ketut Deni Wijaya (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The Indonesian Catholic Church develop multicultural education in the Catholic lesson at 12th grade. In the midst of radicalism that is growing stronger, the effect of Catholic lesson for the growing of multicultural culture of the Catholic young people needs to be questioned. This reseach was conducted toward Catholic students of 12th grade at Madiun city. From the research, can be concluded that multicultural education in the Catholic lesson is still cognitive. Respect for other religions grows better because of family education and brotherhood. Multicultural education needs to develop in cognitive, affective and psycomotor dimensions.